The Military Trial of the Civilians: The Limits of Interpretation and Unwritten Judicial Policy in Pakistan - Imran, Malik Muhammad; Makhdoom, Fakhar Mahmood (Journal of Development and Social Sciences, 2024)
This article provides overview of the history of civilians’ military trials under highly debated Principle of Necessity. The objective is to show the functioning of the courts on the basis of unwritten law and unwritten judicial policy in the operation of the legal system in matters involving civilians’ trials in military courts vis-a-vis the constitutionally granted fundamental rights of due process and a fair trial. This is accomplished by giving brief background, extensive case law and by conducting cross-sectional analysis of the relevant constitutional provisions. This article has concluded that these Courts' attitude might be described as “in defence of leftover continuity." It doesn't seem like the same has the intention of permanently resolving the finding. It is suggested that there is need to arrest the unwritten law based approach of the courts and that it is vital to refrain from making additional decisions when doing so is not required.